A survey of literature examining farmland prices: A Canadian focus. (23rd May 2022) - Deaton, B. James; Lawley, Chad
Abstract: This study assesses agricultural economics literature on farmland prices and key determinants of these prices. The first section of the paper uses a basic capitalization model to organize a review of the literature and data. We then provide a focused assessment of five streams of literature examining farmland prices: (1) boom‐bust; (2) the capitalization effect of government agricultural subsidies on farmland prices; (3) agricultural zoning; (4) climate change; and (5) prohibitions against non‐local buyers of farmland. Our review highlights challenges to ongoing efforts to model changing farmland prices, the modern emphasis on econometric identification, important variation in the magnitude of estimated relationships across the literature, and the opportunity to expand research in Canada. Résumé: Cette étude évalue la littérature en économie agricole concernant les prix des terres agricoles et les principaux déterminants de ces prix. La première section de l'article utilise un modèle de capitalisation de base pour organiser une revue de la littérature et des données. Nous fournissons ensuite une évaluation ciblée de cinq courants de littérature examinant les prix des terres agricoles : (1) boom‐bust; (2) l'effet de capitalisation des subventions agricoles gouvernementales sur les prix des terres agricoles; (3) zonage agricole; (4) changement climatique; et (5) les interdictions contre les acheteurs non locaux de terres agricoles. Notre examen met en évidence les défis des efforts continus pour modéliser l'évolution des prix des terres agricoles, l'emphase plus récente sur l'identification économétrique, l'importante variation de l'ampleur des relations estimées dans la littérature, ainsi que la possibilité d'élargir la recherche au Canada.